2009
DOI: 10.1542/peds.2008-0999
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Hunter Syndrome

Abstract: Hunter syndrome is a rare, X-linked disorder caused by a deficiency of the lysosomal enzyme iduronate-2-sulfatase. In the absence of sufficient enzyme activity, glycosaminoglycans accumulate in the lysosomes of many tissues and organs and contribute to the multisystem, progressive pathologies seen in Hunter syndrome. The nervous, cardiovascular, respiratory, and musculoskeletal systems can be involved in individuals with Hunter syndrome. Although the management of some clinical problems associated with the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
173
1
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 84 publications
8
173
1
13
Order By: Relevance
“…Multiple sulfatase deficiency was excluded by detection of normal activity of other lysosomial sulfatases. The phenotype was judged as "attenuated" and "severe" by pediatricians with expertise in metabolic disorders according to the classification recently published by Muenzer et al 3 Eleven patients presented with the "attenuated" phenotype (mean age 15 years; age range 4.5-32 years), while 22 were classified as the "severe" phenotype (mean age 10.5 years; age range 2.5-19 years).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sulfatase deficiency was excluded by detection of normal activity of other lysosomial sulfatases. The phenotype was judged as "attenuated" and "severe" by pediatricians with expertise in metabolic disorders according to the classification recently published by Muenzer et al 3 Eleven patients presented with the "attenuated" phenotype (mean age 15 years; age range 4.5-32 years), while 22 were classified as the "severe" phenotype (mean age 10.5 years; age range 2.5-19 years).…”
Section: Subjectsmentioning
confidence: 99%
“…In the attenuated form, clinical signs and symptoms occur later, the neurologic deficit is minimal or absent, and patients may survive until late adulthood. 2,3 ERT with recombinant human iduronate-2-sulfatase (idursulfase; Elaprase, Shire Human Genetic Therapies, Cambridge, Massachusetts) has been shown to improve many signs and symptoms of the disease. 1 However, the true impact on the central nervous system and skeletal and skull abnormalities is still debated.…”
mentioning
confidence: 99%
“…Somatic involvement in patients without cognitive impairment can range from being severe with early onset to much less severe with later onset (Young et al 1982;Young and Harper 1983;Neufeld and Muenzer 2001;Schwartz et al 2007;Wraith et al 2008b); this group of patients usually exhibits minimal or no neurological involvement. Management of patients with MPS II requires a multidisciplinary approach involving a range of specialties such as cardiology, neurology, psychology, pulmonology and orthopaedics (Wraith et al 2008a;Muenzer et al 2009;Scarpa et al 2011). Disease-specific treatment in the form of enzyme replacement therapy (ERT) with recombinant I2S (idursulfase [Elaprase®]; Shire, Lexington, MA, USA) became available in the USA in 2006 and Europe in 2007, and alleviates many of the somatic signs and symptoms of the disorder (Muenzer et al 2011); before this, symptomatic management was the only possible treatment approach.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence reported since that time has suggested that earlier treatment before irreversible organ damage occurs may improve clinical outcomes and growth (Muenzer et al 2012;Muenzer et al 2009, SchulzeFrenking et al 2011. A recent 53-week, open-label, safety trial of 0.5 mg/kg weekly idursulfase in children aged 1.4-7.5 years (n ¼ 28) has been completed (Giugliani et al 2013).…”
Section: Introductionmentioning
confidence: 99%